Environmental, Social and Governance (ESG) and Sustainable Development Goals (SDG) the Brazilian Construction Industry: Between Strategic Recognition and the Absence of Measurable Commitments to the 2030 Agenda - Silva Filho, Cândido Ferreira da; Benedicto , Samuel Carvalho de; Ferrari, Vinícius Eduardo; Sugahara, Cibele Roberta; Ferreira, Denise Helena Lombardo; Costa, Matheus Invernizzi (Fronteira: Journal of Social, Technological and Environmental Science, 2026)
The world faces complex social and environmental challenges that demand urgent solutions. In response to these challenges, the United Nations (UN) launched the 2030 Agenda for Sustainable Development in 2015, structured around the Sustainable Development Goals (SDGs). This agenda aims to eradicate extreme poverty and hunger, ensure quality lifelong education for all, protect the planet, and promote peaceful, inclusive, and sustainable societies by 2030. Within this framework, companies have been called upon to contribute to achieving the proposed goals and targets. The management model based on Environmental, Social, and Governance (ESG) dimensions—gaining relevance since 2004—seeks to foster a more just world through sustainable outcomes in social, environmental, and corporate governance aspects, grounded in transparency and responsibility. This study aimed to assess the extent to which the Brazilian construction industry aligns with sustainability principles, the Sustainable Development Goals (SDGs), and the Environmental, Social, and Governance (ESG) principles. Methodologically, it is qualitative, descriptive research of bibliographic and documentary nature. The results indicate that sustainability is a strategic element for the competitiveness of construction companies, contributing to value creation and business longevity. It is observed that firms acknowledge ESG as the foundation of their management model, although distinct from the SDG framework. Furthermore, 50% of the companies analyzed do not present commitments, targets, indicators, or materiality analyses related to the SDGs. As an opportunity for improvement, the need for greater transparency in disclosing indicators, goals, and achieved outcomes is highlighted, allowing stakeholders to monitor the social and environmental impacts of construction company activities.